Music over Manhattan - Karlins, Mark.; Davis, Jack E. (New York : Bantam Doubleday Dell Pub. Group, 1998)
Perfect Cousin Herbert always gets all the attention until Uncle Louie starts teaching Bernie how to play the trumpet.
"A Doubleday book for young readers".
Publisher's Weekly.
Booklist.
L.A. Recommended Foreign Language.
4.7
K-3
Keywords: Trumpet -- Fiction; Cousins -- Fiction; Music -- Fiction; Trumpets -- Fiction; Cousins -- Fiction; Music -- Fiction; Trumpet -- Fiction; Cousins -- Fiction; Music -- Fiction; New York (N.Y.) -- Fiction; New York (N.Y.) -- Fiction; New York (N.Y.) -- Fiction